Kontribusi Digitalisasi Bisnis Dalam Menyokong Pemulihan Ekonomi dan Mengurangi Tingkat Pengangguran di Indonesia - Agus Rohmat Hidayat; Nur Alifah; Agis Ahmad Rodiansjah (Syntax Idea)
This study analyzes the factors affecting the unemployment rate in Indonesia by focusing on three important aspects: global description, the role of the government in reducing unemployment, and the role of e-commerce or business digitalization in minimizing unemployment. The results of the analysis show the complexity and variety of factors affecting unemployment, including the significant impact of the COVID-19 pandemic on the economy and labor market. The role of government in formulating economic policies, workforce training, and social protection has major implications in reducing unemployment. In addition, technology and business digitalization through e-commerce also make a positive contribution in creating new jobs and independent job opportunities. However, to achieve a sustainable reduction in unemployment, an integrated approach is needed that considers economic dynamics, cooperation between different sectors, and adaptation to continuous changes in society.